Prevalence of gastrointestinal symptoms after recovery from COVID-19: A questionnaire-based study in the Aseer region - Mohammed Attieh Alzahrani; Khalid Siraj Altalhiyyah; Mohammed Mousa Albariqi; Meshal Ali Alkhayri; Saad Ali Alshahrani; Sultan Saad Alnasser; Nawaf Mohammed Alshehri; Saad Haif Alqahtani; Saud Haif Alqahtani (SAGE Open Medicine)
Background: The coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide, and although it is primarily a respiratory illness, gastrointestinal symptoms have been reported in a significant proportion of patients. Aim: Prevalence of gastrointestinal symptoms after recovery from COVID-19. Methodology: A community-based cross-sectional study was conducted in the Aseer region of Saudi Arabia. The study population included individuals aged 18 years or older with COVID-19 and living in the Aseer region. The data were collected through a pretested, structured online questionnaire preceded by consent and were used to maintain the confidentiality of the data. The questionnaire covered participants’ data, COVID-19 infection status, and gastrointestinal tract symptoms during and after recovery from the infection. Results: A total of 409 participants in the Aseer region completed the study survey. The participants’ ages ranged from 18 to more than 50 years, with a mean age of 34.5 ± 11.9 years. A total of 205 (50.1%) participants were females. A total of 263 (64.3%) of the study participants experienced gastrointestinal tract symptoms during COVID-19 infection. Additionally, 203 (49.6%) of the study participants had gastrointestinal tract symptoms after recovering from COVID-19 infection. The most commonly reported symptoms were diarrhea (13.2%), nausea (13.2%), anorexia (12.7%), abdominal pain (11%), and constipation. Male sex who suffered form severe COVID-19 infection, and gastrointestinal tract symptoms during acute infection were significantly associated with post-COVID-19 gastrointestinal tract symptoms ( p  < 0.05). Conclusions: In conclusion, the current study showed that nearly two-thirds of active COVID-19 patients experienced gastrointestinal tract symptoms. Additionally, approximately half of the COVID-19 patients who recovered had gastrointestinal tract-related symptoms, but few of those patients had gastrointestinal tract-related symptoms within 1 week.